The Arabic Participle: Between an Adjectival Phrase and a Relative Clause - Dizdar, Elma (Prilozi za orijentalnu filologiju, 2019)
Participles used as adjectival phrases and relative clauses stand as mutually opposed in terms of syntactic features, but also fairly close, since both serve as noun phrase modifiers. They are therefore often described as „competing“ structures. The focus of this paper is to analyse participial structures in the Arabic language and the way they codify different syntactic positions of the antecedent, i.e. the directive element of a noun phrase. It shows that, due to relativizing strategies taken from the Arabic relative clause, as well as the inherent features of the Arabic morphology, participles are, in fact, much closer to relative clauses in Arabic than in other languages. One of the consequences of this closeness of participles and relative clauses in Arabic are the structures which do not allow for a clear line to be drawn so as to characterise them as either participles or relative clauses. Moreover, Arabic also frequently, even systemically uses participial structures that may be translated into other languages only as relative clauses. It is thus possible to say that Arabic participles are also successful „competitors“ of relative clauses.